Uji In Vitro Aktivitas Antibakteri Ekstrak Bawang Dayak (Eleutherine bulbosa) Terhadap Isolat Klinis - Frans Grovy Naibaho; Anita Maulina; Liswara Neneng (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
Dayak onion (Eleutherine bulbosa) is a medicinal plant that has been known and used by Dayak People from Central Kalimantan. It contains various chemical compounds such as alkaloids, glycosides, flavonoids, phenolics, steroids, and tannins which are known to have antibacterial effects. This study aimed to determine the antibacterial activity of Dayak onion extract against two pathogenic bacteria namely Escherichia coli and Staphylococcus aureus in vitro and to determine the minimum inhibitory concentration (MIC) value of the Dayak onion extract. Extraction was carried out by maceration method using ethanol 96 % and n-hexane. The antibacterial activity test was carried out using the disc diffusion method (Kirby-Bauer Test). The determination of MIC value was carried out by using disc diffusion with five different concentrations 500, 250, 100, 50, 25, and 10 mg/mL. The research result showed that Dayak onion had antibacterial activity. Ethanol 96% extract was only able to inhibit the growth of S. aureus with an inhibition zone of 15.02 mm. Meanwhile, the n-hexane extract was able to inhibit the growth of S. aureus and E. coli with an inhibition zone of 18.48 dan 14.94 mm, respectively. MIC value of ethanol 96% for S. aureus was 50 mg/mL. N-hexane extract has MIC value for E. coli and S. aureus was 10 mg/mL.